An Analysis The Types Of Directive Illocutionary Acts By The Characters Found In “Trolls 2016” Movie - Suci Lestari, Ni Putu; Agoes Caskara Surya Putra, I Gede (CV. Multi Kreasi Media, 2024)
The occurence of illocutionary acts in a movie is a common phenomenon that appears in characters’ dialogue. This study aims to answer the research problem especially the types of directive illocutionary acts in the selected utterances expressed by the characters in “Trolls” movie (2016). This research only focuses on 4 kinds of directive illocutionary act, namely commanding, ordering, requesting, and suggesting. This study is conducted by using descriptive qualitative method and the data were analyzed based on the theory of Yule (1996) to distinguish the types of directive illocutionary acts that found in the movie. There were 254 data that are related to the types of directive illocutinary acts as the findings of this study. Commanding act becomes the most dominant directive illocutionary acts occured in this research, it provides 98 utterances from 254 utterances. On the other hand, the second dominant type of directive illocutionary acts is suggesting act which shows 68 utterances. Then, it is followed by 54 utterances of ordering act and the least occurence is 34 utterances of requesting act.